Summary of the Key Concepts on How to Develop a Perinatal Palliative Care Program - Lago, Paola; Cavicchiolo, Maria Elena; Rusalen, Francesca; Benini, Franca (Frontiers in Pediatrics, 2020)
Purpose of review: The aim of this study is to assess the most significant Perinatal Palliative Care (PnPC) development projects in the literature and summarize the shared key principles. Recent findings: PnPC is a new concept in neonatal intensive care approach. Advancements in perinatal diagnostics and medical technology have changed the landscape of the perinatal world. The threshold of viability continues to decrease, and diagnostic information is available earlier in pregnancy and more rapidly at the bedside; overall outcomes continue to improve. This rapid technological improvement brings ethical debates on the quality of life of patients with life-limiting and life-threatening conditions and the need to involve the family in the decision-making process, according to their wishes and cultural beliefs. Although the Perinatal Hospice concept was developed in the 1980s in the US, the first recommendations on how to develop a PnPC pathway were published in the early 2000s. We considered the most relevant position statements or guidelines on PnPC published in the last two decades. Some of them were more pertinent to pediatrics but still useful for the fundamental concepts and PnPC project’s development. Summary: Health care providers and institutions are encouraged to develop PnPC programs, which have the goal of maximizing the quality of life of infants with non-curable conditions. These may generally include the following: a formal prenatal consultation; development of a coordinated birth plan between obstetrician, newborn care, and family; access to other neonatal and pediatric specialties, as needed; comfort palliative care during the prenatal, birth, and postnatal periods; and emotional support for families, siblings, and staff.